Efficacy of Sofosbuvir and Ribavirin in Children Presenting with Hepatitis C at Tertiary Care Hospital, Faisalabad - Nagina Shahzadi; Naureen Kanwal Satti; Huma Arshad; Nadeem Hashmat (Journal of Bahria University Medical and Dental College)
Objectives: To assess efficacy, safety, and outcome of combination of Sofosbuvir and Ribavirin in various genotypes, in children with hepatitis C infection. Study design and setting: It was a quasi-experimental study, conducted at the Gastroenterology and Hepatology Department, Children Hospital Faisalabad, from August 2017 to August 2021. Methodology: 50 confirmed cases of HCV infection aged 5 to 18 years, were given an oral dose of Sofosbuvir and Ribavirin daily for 12 weeks. PCR was assessed at 4 weeks (for Rapid Viral Response (RVR)) and repeated at 8 weeks and 12 weeks (for Early Viral Response (EVR)) and again 12 weeks after the completion of therapy for Sustained Viral Response (SVR)). Primary outcome was the number who achieved an SVR at 12 weeks (SVR12) after completion of treatment with a viral load below quantitation level. Results: Genotype 3 was found in 80% , type 1 in 6% , type 2 in 4% and 10% were untypeable. All children were PCR positive at presentation; 96% became PCR negative at 4 weeks (RVR), while 100 percent were negative at 8 weeks, 12 weeks (EVR), and SVR 12 weeks after completion of 12 week course was 100%. Conclusion: Although majority of patients were Genotype 3, 12 week course of Sofosbuvir and Ribavirin of hepatitis C-infected children was highly effective, with 100 percent PCR-negative cases at 8 weeks and 12 weeks with only minor side effects, and, SVR of 100% twelve weeks after completion of therapy